Pengaruh Pemahaman Akuntansi, Pengalaman dan Tantangan Terhadap Implementasi SAK EMKM Pada UMKM di Surakarta - Alfa Pabela Pratama; Fadjar Harimurti (Journal of Innovative and Creativity (Joecy), 2026)
This study aims to analyze the influence of understanding, experience, and challenges faced by MSME actors on the implementation of Financial Accounting Standards for Micro, Small, and Medium Entities (SAK EMKM) in Surakarta City. The research employs a quantitative approach with a survey technique, where data was collected through questionnaires distributed to MSME actors in the furniture sector. Multiple linear regression with classical assumption tests was used for data analysis. The results indicate that accounting understanding and experience have a significant positive effect on the implementation of SAK EMKM, while challenges do not have a significant effect. The study highlights the importance of enhancing accounting understanding and experience in supporting transparency of MSME financial reporting.